Dietary Supplementation With Xylo-oligosaccharides Modifies the Intestinal Epithelial Morphology, Barrier Function and the Fecal Microbiota Composition and Activity in Weaned Piglets - Su, Jiayi; Zhang, Wanghong; Ma, Cui; Xie, Peifeng; Blachier, Francois; Kong, Xiangfeng (Frontiers in Veterinary Science, 2021)
The present study determined the effects of dietary xylo-oligosaccharide (XOS) supplementation on the morphology of jejunum and ileum epithelium, fecal microbiota composition and metabolic activity, and expression of genes related to colon barrier function. A total of 150 piglets were randomly assigned to one of five groups: a blank control group (receiving a basal diet), three XOS groups (receiving the basal diet supplemented with 100, 250, and 500 g/t XOS, respectively), as well as a positive control group used as a matter of comparison that received the basal diet supplemented with 0.04 kg/t virginiamycin, 0.2 kg/t colistin, and 3000 mg/kg ZnO. The trail was carried out for 56 days. The results showed that the lowest dose tested (100 g/t XOS) increased (P < 0.05) the ileal villus height, the Lactobacillus relative amount, and acetate concentration in feces, while decreasing (P < 0.05) the fecal Escherichia coli relative amount and the expression of the inflammatory cytokines IL-1β and IL-8 in colon, when compared with the blank control group. In conclusion, dietary 100 g/t XOS supplementation modifies the intestinal ecosystem is a way that is compatible with beneficial effects in weaned piglets.